2008
DOI: 10.1186/bcr1843
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of HER1/EGFR, HER2, HER3 and HER4 in 278 breast cancer patients

Abstract: Introduction The HER (human EGFR related) family of receptor tyrosine kinases (HER1/EGFR (epidermal growth factor receptor)/c-erbB1, HER2/c-erbB2, HER3/c-erbB3 and HER4/ c-erbB4) shares a high degree of structural and functional homology. It constitutes a complex network, coupling various extracellular ligands to intracellular signal transduction pathways resulting in receptor interaction and cross-activation. The most famous family member is HER2, which is a target in Herceptin™ therapy in metastatic status a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 54 publications
5
126
2
2
Order By: Relevance
“…In addition, we demonstrated a positive association between HER2 and HER3 mRNA expression. A similar correlation was described earlier, both at the mRNA and protein level (Bieche et al, 2003;Witton et al, 2003;Sassen et al, 2008). It has been suggested that the HER2/HER3 heterodimer constitutes the most mitogenic dimer in the HER family (Citri et al, 2003).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, we demonstrated a positive association between HER2 and HER3 mRNA expression. A similar correlation was described earlier, both at the mRNA and protein level (Bieche et al, 2003;Witton et al, 2003;Sassen et al, 2008). It has been suggested that the HER2/HER3 heterodimer constitutes the most mitogenic dimer in the HER family (Citri et al, 2003).…”
Section: Discussionsupporting
confidence: 65%
“…A number of studies evaluating HER family receptors have indicated a negative prognostic value of HER3 in breast cancer patients (Bieche et al, 2003;Witton et al, 2003;Sassen et al, 2008). In contrast, our present study showed a positive association between HER3 mRNA expression and OS.…”
Section: Discussioncontrasting
confidence: 56%
“…The role of Her4 in breast cancer development has been considered ambiguous, partly because of a lack of mechanistic knowledge about its mode of action (21, [31][32][33][34][35]. In this context, our study sheds light on the mechanism of action of Her4 by showing that its active form is required to stabilize the MDMX-MDM2 complex, as we demonstrated using a ␥-secretase inhibitor to prevent Her4 activation in response to NRG1 stimulation.…”
Section: Discussionmentioning
confidence: 91%
“…Her4 signal (35). With the search criteria based on high stringency, the software identified two candidate kinases, CDK4/6 and p38 (Fig.…”
Section: Cdk4/6 Mediates Her4 Stabilization Of Mdmx-mdm2 and Its Suppmentioning
confidence: 99%
“…85 Several studies have demonstrated that HER3 is frequently co-expressed with HER2 in breast cancer, and HER3 has a role in HER2-mediated breast carcinogenesis. 86,87 Iorio et al 81 suggested that the reintroduction of miR-205 into SKBr3 cell increases the responsiveness of lapatinib (tyrosine kinase inhibitors) avoiding HER3-mediated resistance and restoring potent proapoptotic activity. Wang et al 88 predicted that miR-205 binds to the 3′ untranslated regions of HER3 mRNA, and the upregulation of miR-205 reduced HER3 protein expression.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%